Analysis of Time Management Implementation Using the Crashing Method on the Rehabilitation Project of the Disdikbudpora Hall Building in Semarang Regency - Ramadhany, Shinta Ayu; Suwandi, Putri Anggi Permata; Husodo, Ibnu Toto (Science and Technology Research Centre, Universitas PGRI Semarang, 2026)
This study analyzes the application of time management using the crashing method on the Rehabilitation Project of the Disdikbudpora’s Hall Building in Semarang Regency. This project has an implementation period of 57 calendar days. To assess whether this duration could be optimized, the crashing method was applied to critical path activities by adding overtime work hours (1 to 3 hours/day). The research utilized a qualitative method with a quantitative approach, using primary data from field observations and secondary data such as schedules and weekly reports. Results showed that by adding 1, 2, and 3 hours of overtime, the project duration could be reduced to 54, 49, and 48 days, respectively. Cost analysis revealed that adding 2 hours of overtime provided the most optimal balance between shortened duration and additional labor costs, totaling IDR 58,556,562.50. This option offered a 5 day acceleration with a relatively small cost difference compared to 1 hour overtime. Therefore, adding 2 hours of overtime is considered the most efficient strategy for project acceleration.